REPRODUCTIVE CYCLE OF THE ESTUARINE BIVALVE MERETRIX MERETRIX (LINN) OF THE VELLAR ESTUARY - Jayabal, R; Kalyani, M (Indian Journal of Fisheries, 2011)
The hard clam, Meretrix mereirix ’(L), in VeMar estuaiy haÂ® an extended breeding period from February to September and the maturation of gonads takes place immediately after spawning. Both males, which are slightly more dominant, and females attain maturity at the same size. The spat settlement starts from March onwards. Among the ecological factors, salinity is found to play an importaiit role in the reproductive cycle.